Analisis Manajemen Perkreditan untuk Meningkatkan Profitabilitas pada Bank BNI Wilayah VII Makassar - Sitti Marhumi (LP3M Universitas Muhammadiyah Makassar)
The research is intended to find out the credit management of Bank BNI Region VII Makassar, by using a type of qualitative and quantitative data. The source of the data used primary and secondary data. The analytical method used is the method of Rate Of Return On Loans, Interest On Loans Margin, and Return On Assets based on the Annual Report of the year 2012 to 2014. This research is useful to obtain information concerning the increase profitability through the credit management. The results showed that Credit Management is not able to Increase profitability.